الأسس العملية الحديثة في إدارة وتسيير الجماعات المحلية في إطار معادلة عصرنة محلية - تنمية محلية - لعمري، محمد Lameri, Mohammed (جامعة محمد خيضر بسكرة - كلية الحقوق والعلوم السياسية - مخبر أثر الاجتهاد القضائي على حركة التشريع, 2020)
تعتبر عصرنة التسيير المحلي رهانا فرض نفسه على الدولة حيث عمدت إلى مراجعة أنماطه بآليات تمكن من تكريس استقلالية الجماعات المحلية وتعزز دورها الريادي في التنمية وذلك بالانتقال من تسيير كلاسيكي رويتني إلى تسيير استشرافي يتماشى مع المستجدات الاقتصادية والسياسية والاجتماعية ويستجيب لتطلعات المواطن بما يحقق لامركزية التسيير في إطار التنمية المستدامة. وبما أن ارتباط وجوارية الجماعات المحلية بالمواطن والمتعاملين الاقتصاديين يمثل المحور الرئيسي لنجاح السياسة الوطنية عمدت السلطات العمومية الجزائرية في الآونة الأخيرة إلى اتخاذ عدة إجراءات عملية جعلت الجماعات المحلية على خط موازي مع الاستراتيجية الوطنية وفق آليات تدخل تمكنها من تحقيق تنمية محلية من أهمها تحرير المبادرات المحلية التي تثمن وتضاعف إمكانياتها وثرواتها.
The modernization of local management is considered a bet that imposed itself on the state, as it deliberately revised its patterns with mechanisms that enable the independence of local groups and enhance their pioneering role in development, by moving from a classic, routine management to a forward-looking management in line with economic, political and social developments and responding to the aspirations of the citizen in a way that achieves decentralization of management within the framework sustainable development. And since the association and neighborhood of local groups with citizens and economic dealers is the main axis for the success of the national policy, the Algerian public authorities have recently taken several practical measures that put the local groups on a parallel line with the national strategy according to intervention mechanisms that enable them to achieve local development, the most important of which is the liberation of local initiatives. That value and multiply its capabilities and wealth.
Keywords: القانون الإداري -- الإدارة المحلية -- التنمية المستدامة -- التنظيم الإداري